Pengaruh Kepemimpinan Instruksional Kepala Sekolah, Lingkungan Kerja dan Kepuasan Kerja terhadap Kinerja Guru SMA Negeri - Eko Sanyoto; Sulaiman Sulaiman; Muhyani Rizalie (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research analyzes the direct and indirect influence of the principal's instructional leadership, work environment, and job satisfaction on teacher performance at SMAN Kota Banjarbaru. The method used in this research is descriptive correlational, using a path analysis model to analyze the influence between variables. The research population was 163 teachers from 4 high schools in the Banjarbaru area, and 116 respondents were taken as research samples using the Slovin formula with the Proportionate Random Sampling technique. Data collection uses questionnaire instruments, and data analysis uses descriptive analysis, prerequisite tests, inferential tests, and path analysis. The results of the study of the regression coefficient values ​​of the principal's instructional leadership variable on teacher performance were 0.327, the work environment variable on teacher performance was 0.334, the job satisfaction variable on teacher performance was 0.331, the principal's instructional leadership variable on the work environment was 0.876, the principal's instructional leadership variable on job satisfaction of 0.858, the principal's instructional leadership variable on teacher performance through the work environment is 0.293 and the principal's instructional leadership variable on teacher performance through job satisfaction is 0.284. In conclusion, there is a direct or partial influence of the principal's instructional leadership variables, work environment, and job satisfaction on the performance of high school teachers, and there is an indirect influence of the principal's instructional leadership on the performance of teachers in high school through intermediary media, either work environment or job satisfaction. Keywords: Instructional Leadership, Environment, Satisfaction, Performance